Pengaruh Kinerja Petugas dan Fasilitas Pelayanan Ruang Tunggu terhadap Kepuasan Penumpang di Bandar Udara Sultan Muhammad Salahuddin Bima - Abdurrahman Abdurrahman (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
The Effect of Officer Performance and Waiting Room Service Facilities on Passenger Satisfaction at Sultan Muhammad Salahuddin Airport, Bima. Author : Abdurrahman. The progress of science and innovation is currently getting faster and changing. This is very much felt in the field of aviation, both local airlines and logging around the world. The need for a destination is also felt by passengers to choose transportation services including air transportation that is able to carry their journey to reach the passenger's destination quickly, safely and fairly according to their financial needs. To see if the performance of officers and service facilities has a synchronous impact on passenger satisfaction at Sultan Muhammad Salahuddin airport, Bima. This study uses quantitative testing with an overview of the selected strategy as important information using a questionnaire. The population that will be used in this study are passengers who use waiting room facilities at Sultan Muhammad Salahuddin airport, Bima. on a sample of 60 respondents. The data analysis technique used the help of IMB SPSS statistics21. The results showed a significance value of 0.000 <0.05. This shows that there is a positive influence on the performance of officers and waiting room service facilities on customer satisfaction at Sultan Muhammad Salahuddin airport, Bima. Based on the Officer Performance variable (X1), the t-count is 4.817, the service facility variable (X2) is 5.311 t-count is obtained which is considered significant 0.000 <0.05 so H1 or H2 is accepted, meaning that the Officer Performance variable (X1) and service facilities ( X2) waiting room has an effect on passenger satisfaction (Y). From the results of this review, it is known that the calculated F value is 54,025 with a total significance of 0.000 <0.05. So it can be concluded that the variables of Officer Performance (X1) and Service Facilities (X2) waiting room significantly have a positive and significant influence on Passenger Satisfaction (Y) at Sultan Muhammad Salahuddin Airport Bima. Keyword: Kinerja, Fasilitas Pelayanan, Kepuasan penumpang